1996
DOI: 10.1021/es950421u
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Solubility Domain Approach for the Modeling of the Hydroxide Precipitation of Heavy Metals from Wastewater

Abstract: The use of the solubility domain approach for providing representative effluent treatment quality assurance standards for the hydroxide precipitation of Zn 2+ , Pb 2+ , and Fe 3+ from various wastewater composition types has been modeled and experimentally validated. Solubility domain calculations were based on the precipitated phases isolated from systems representing the upper and lower limits of potential effluent chemical compositions. All such phases resembled their mineralized counterparts with a lower d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The formation of CdSO 4 ·3.5Cd(OH) 2 ·xH 2 O and/or β-Cd(OH) 2 and CaSO 4 ·2H 2 O as separate phases suggests that no Ca 2+ -Cd(II) multi-component solid species occur during the hydroxide precipitation of Cd(II) from a SO 4 2− -rich environment in the presence of Ca 2+ . Moreover, the formation of CaSO 4 ·2H 2 O had little effect on the solubility of Cd(II), which is in agreement with previous observations in SO 4 2− -rich systems Baltpurvins et al, 1996). These studies also demonstrate the effect that Ca 2+ has on the nature of solid phases actually isolated.…”
Section: Cd(ii)/sulfate System (Ca 2+ and Mg 2+ Systems)supporting
confidence: 92%
See 3 more Smart Citations
“…The formation of CdSO 4 ·3.5Cd(OH) 2 ·xH 2 O and/or β-Cd(OH) 2 and CaSO 4 ·2H 2 O as separate phases suggests that no Ca 2+ -Cd(II) multi-component solid species occur during the hydroxide precipitation of Cd(II) from a SO 4 2− -rich environment in the presence of Ca 2+ . Moreover, the formation of CaSO 4 ·2H 2 O had little effect on the solubility of Cd(II), which is in agreement with previous observations in SO 4 2− -rich systems Baltpurvins et al, 1996). These studies also demonstrate the effect that Ca 2+ has on the nature of solid phases actually isolated.…”
Section: Cd(ii)/sulfate System (Ca 2+ and Mg 2+ Systems)supporting
confidence: 92%
“…Previous studies Baltpurvins et al, 1995Baltpurvins et al, , 1996Baltpurvins et al, , 1997aTünay et al, 1991) have shown that the use of chemical speciation packages for the prediction of effluent treatment performance is highly dependent on the nature of the actual solubility-limiting (i.e. solubility-determining) phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is difficult to be removed by conventional hydrolysis precipitation. The addition of oxidizing chemicals is the most popular method to destroy and remove cyanides [2], and then Cd available to be removed by hydrolysis precipitation and coagulation [3,4]. Fe(VI) has been reported to be effective for treating heavy metal-cyanide complex due to cyanide oxidation by Fe(VI) and subsequent removal of heavy metal by Fe(III) coagulation [5,6].…”
Section: Introductionmentioning
confidence: 99%